2022
DOI: 10.3389/fbioe.2022.925339
|View full text |Cite
|
Sign up to set email alerts
|

Application of three-dimensional-printed porous tantalum cones in total knee arthroplasty revision to reconstruct bone defects

Abstract: Purpose: Three-dimensional (3D) printing technology has emerged as a new treatment method due to its precision and personalization. This study aims to explore the application of a 3D-printed personalized porous tantalum cone for reconstructing the bone defect in total knee arthroplasty (TKA) revision.Methods: Between November 2017 and October 2020, six patients underwent bone reconstruction using 3D-printed porous tantalum cones in TKA revision. The knee function was assessed using the Hospital for Special Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In addition, Wang et al [104] documented a case study of an 83 year-old female patient suffering from chronic inflammation, tibial prosthesis loosening with bone loss, and severe osteoporosis who was treated with personalized 3D-printed porous pure tantalum pads assisting a left total knee arthroplasty (TKA) with good postoperative recovery and good follow-up results. Moreover, a study conducted by Ao et al [107] demonstrated the use of 3D-printed porous tantalum cones in bone reconstruction for six patients who had undergone revision TKA. The postoperative follow-up revealed that the implanted joint achieved vertebral stabilization, effectively repairing metaphyseal bone defects in the knee and enhancing joint function and quality of life.…”
Section: Application Of Porous Tantalum Bone Scaffoldsmentioning
confidence: 99%
“…In addition, Wang et al [104] documented a case study of an 83 year-old female patient suffering from chronic inflammation, tibial prosthesis loosening with bone loss, and severe osteoporosis who was treated with personalized 3D-printed porous pure tantalum pads assisting a left total knee arthroplasty (TKA) with good postoperative recovery and good follow-up results. Moreover, a study conducted by Ao et al [107] demonstrated the use of 3D-printed porous tantalum cones in bone reconstruction for six patients who had undergone revision TKA. The postoperative follow-up revealed that the implanted joint achieved vertebral stabilization, effectively repairing metaphyseal bone defects in the knee and enhancing joint function and quality of life.…”
Section: Application Of Porous Tantalum Bone Scaffoldsmentioning
confidence: 99%
“…The biological response to the host bone, on the other hand, is usually achieved by monolithic or surface modification of such implants [ 9 ]. In just the past few years, metal 3D printing technology in the medical field, especially the application of orthopedics has been highly valued, and its innovative potential and application prospects are more generally favored [ 50 , 108 , [184] , [185] , [186] , [187] , [188] ]. Several metal 3D printing orthopedic implant applications are shown in Fig.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…To date, research on the clinical application of patient-specific implants has focused on bone tumor surgery, joint replacement surgery, spinal implants, and traumatic fracture fixation and reconstruction as listed in Table 3 , Table 4 , Table 5 , Table 6 .
Figure 4 Clinical application of metal 3D printing orthopedic implants (A) Radial head prosthesis [ 184 ], (B) Porous scaffolds in femoral defect [ 108 ], (C) Total talus implant [ 185 ], (D) Spine fusion device [ 186 ], (E) Trabecular acetabular cup [ 187 ], (F) Cones in total knee arthroplasty [ 188 ], reproduced with permission.
…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Bone tissue grows normally only when it is subjected to an appropriate mechanical load. Insufficient force will cause bone absorption, whereas excessive stress can destroy the bone tissues ( Ao et al, 2022 ).…”
Section: Mechanical Propertiesmentioning
confidence: 99%